Always on My Mind? Recognition of Attractive Faces May Not Depend on Attention - Silva, André; Macedo, António F.; Albuquerque, Pedro B.; Arantes, Joana (Frontiers in Psychology, 2016)
Little research has examined what happens to attention and memory as a whole when humans see someone attractive. Hence, we investigated whether attractive stimuli gather more attention and are better remembered than unattractive stimuli. Participants took part in an attention task - in which matrices containing attractive and unattractive male naturalistic photographs were presented to 54 females, and measures of eye-gaze location and fixation duration using an eye-tracker were taken - followed by a recognition task. Eye-gaze was higher for the attractive stimuli compared to unattractive stimuli. Also, attractive photographs produced more hits and false recognitions than unattractive photographs which may indicate that regardless of attention allocation, attractive photographs produce more correct but also more false recognitions. We present an evolutionary explanation for this, as attending to more attractive faces but not always remembering them accurately and differentially compared with unseen attractive faces, may help females secure mates with higher reproductive value.